Application of Magnetic Integrated Technology in Controllable Reactor of Transformer Type - Jianning Yin; Mingxing Tian; Guohan Yin (Institute of Advanced Engineering and Science, 2014)
There is the magnetic coupling among control windings of controllable reactor of transformer type (CRT), the decoupling integrated magnetic technology is applied to the structure design of CRT in this paper. To realize the decoupling among the control windings we propose a magnetic integrated structure of CRT by providing low magnetic resistance magnetic circuit for control windings magnetic flux. The winding leakages of this structure are calculated, its inductance-transformer equivalent circuit is also established, and the equation of the coupling degree of control windings and no-load current with the lateral column air gap size are deduced. The simulation model for a CRT is fabricated with MATLAB/SIMULINK. Simulation and analysis results shows that when increasing the air gap, the magnetic coupling between the control windings decreases apparently, the utilization ratio of windings current is also raised. The simulation results verify the effectiveness of this method by controlling the lateral column air gap size to achieve the purpose of decoupling.